Development and evaluation of a secondary reference panel for BCR-ABL1 quantification on the International Scale - Cross, Nicholas C. P.; Dietz, Christian; Müller, Martin Christian (Leukemia, 2016)
Molecular monitoring of chronic myeloid leukemia patients using robust BCR-ABL1 tests standardized to the International Scale (IS) is key to proper disease management, especially when treatment cessation is considered. Most laboratories currently use a time-consuming sample exchange process with reference laboratories for IS calibration. A World Health Organization (WHO) BCR-ABL1 reference panel was developed (MR1-MR4), but access to the material is limited. In this study, we describe the development of the first cell-based secondary reference panel that is traceable to and faithfully replicates the WHO panel, with an additional MR4.5 level. The secondary panel was calibrated to IS using digital PCR with ABL1, BCR and GUSB as reference genes and evaluated by 44 laboratories worldwide. Interestingly, we found that >40% of BCR-ABL1 assays showed signs of inadequate optimization such as poor linearity and suboptimal PCR efficiency. Nonetheless, when optimized sample inputs were used, >60% demonstrated satisfactory IS accuracy, precision and/or MR4.5 sensitivity, and 58% obtained IS conversion factors from the secondary reference concordant with their current values. Correlation analysis indicated no significant alterations in %BCR-ABL1 results caused by different assay configurations. More assays achieved good precision and/or sensitivity than IS accuracy, indicating the need for better IS calibration mechanisms.
Gesehen am 31.07.2019